2020
DOI: 10.1016/j.psj.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in ovo administered pioneer colonizers on intestinal proteome on day of hatch

Abstract: Pioneer colonization of the gastrointestinal tract ( GIT ) by bacteria is thought to have major influence on neonatal tissue development. Previous studies have shown in ovo inoculation of embryos with saline (S), species of Citrobacter (C, C2), or lactic acid bacteria (L) resulted in an altered microbiome on day of the hatch ( DOH ). The present study investigated GIT proteomic changes at DOH in relation to different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 88 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…Additionally, Feng et al found that higher levels of Akt phosphorylation and PI3K activation enhance gut barrier integrity ( 65 ), suggesting SPORE-induced changes of the PI3K/Akt signaling pathway may also contribute to this reduction in gut permeability. Although we did not look at changes in tight junction protein formation and gene expression in this study, ileal spore treatment may have affected these parameters, as in ovo exposure to bacteria induced changes in tight junction signaling ( 47 ). Future studies will evaluate expression of tight junction proteins to allow better-interpretation of gut permeability data.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, Feng et al found that higher levels of Akt phosphorylation and PI3K activation enhance gut barrier integrity ( 65 ), suggesting SPORE-induced changes of the PI3K/Akt signaling pathway may also contribute to this reduction in gut permeability. Although we did not look at changes in tight junction protein formation and gene expression in this study, ileal spore treatment may have affected these parameters, as in ovo exposure to bacteria induced changes in tight junction signaling ( 47 ). Future studies will evaluate expression of tight junction proteins to allow better-interpretation of gut permeability data.…”
Section: Discussionmentioning
confidence: 97%
“…This study showed a consistent trend in which phosphorylation shifts in immunometabolic pathways, mainly innate immunity, were reduced from 3 to 7 dpi. Similarly, single-dose in ovo delivery of Citrobacter species or LAB also altered early inflammatory responses in the chicken gut ( 47 , 48 ). These findings suggest that innate immune responses are highly responsive to microbial “pioneers” in the chicken intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Results were consistent in both exp 1 and 2, indicating that spraying the inoculum on seeder chicks horizontally transmitted the pathogen during hatch ( Table 1 ). Significant differences ( P < 0.0001) in LAB were also observed between the challenged groups and negative control ( Table 1 ), indicating that gram-negative bacteria may contribute to colonization by LAB ( Wilson et al., 2020 ). LAB are naturally found in the GIT of animals ( Reuben et al., 2019 ).…”
Section: Resultsmentioning
confidence: 96%
“…While the 2 Enterobacteriaceae used were both Citrobacter sp. , the proteomic analysis predicted increased inflammation alongside suppression of the ability to respond to inflammation ( Rodrigues et al, 2020 ; Wilson et al, 2020 ). This uncontrolled inflammation can result in a nonbeneficial intestinal environment, suppression of the immune system, and in turn, increased risk of opportunistic infection ( Meirow and Baniyash, 2017 ).…”
Section: Discussionmentioning
confidence: 99%